Galen on pharmacology : philosophy, history, and medicine : proceedings of the Vth International Galen Colloquium, Lille, 16-18 March 1995 - Debru, Armelle. (Studies in Ancient Medicine, 1997)
The 14 papers in this volume were first presented at the Fifth International Galen Colloqium held in Lille in 1995 and represent a first attempt to explore systematically this vast complicated area. The contributors cover a wide variety of themes, broadly grouped as: the epistemology , method and practice of medicine, Galen and pharmacological tradition, Galen's pharmacological treatises and the transmission of pharmacological texts. Their papers shed a new light on this ancient therapeutic field and also help to understand Galen's pharmacology in its relation to the entire body of its work and thought.